THE EFFECT OF THE APPLICATION OF BIOSTIMULATORS ON PLANT GROWTH AND LEAF FORMATION IN THE INTERCROPPING OF MAIZE AND SOYBEAN CROPS - Iminov Abduvali Abdumannobovich (Western European Studies, 2023)
This article presents information on the effect of biostimulants on the growth of plants and the formation of leaves in interplanting of maize "Esdalik-80" and soybean "Uzbek2" varieties. lib, the highest values were observed in the options where Tandem biostimulant was applied at the rate of 400 ml/t before planting seeds, 300 ml/ha during the period of 3-4 leaf formation, and 500 ml/ha during the period of 8-10 leaf formation. , the height of the plant is 19.1/7.3 cm, the number of leaves in one plant is 5.2/5.6 pieces, compared to the control option by 3.0/2.5 cm, the number of leaves and it was found that it was more than 2.1/2.8 units. It was found that the number of leaves was higher by 0.5/1.0 cm, and by 0.6/1.3, compared to the variant in which Fitovak biostimulator was used
Keywords: Maize; soybean; biostimulant; standard